Fuzzy Similarity and Counterfactuals in the Assessment of Default Risk: the Eurozone Crisis and the Argentinean Solution - Pazzi, Jorge (2015)
We present an approach, based on the notion of fuzzy similarity, to the comparison of economies under default risk. We run a counterfactual analysis of the perspectives of the most troubled countries in the Eurozone compared with Argentina in 2001. This allows us to assess the possibility that these economies will end up following the path of Argentina.